Thymosin β4 protects against aortic aneurysm via endocytic regulation of growth factor signaling - Munshaw, S; Bruche, S; Redpath, A; Jones, A; Patel, J; Dube, K; Lee, R; Hester, S; Davies, R; Neal, G; Handa, A; Sattler, M; et al. (American Society for Clinical Investigation, 2021)
Vascular stability and tone are maintained by contractile smooth muscle cells (VSMCs). However, injury-induced growth factors stimulate a contractile-synthetic phenotypic modulation which increases susceptibility to abdominal aortic aneurysm (AAA). As a regulator of embryonic VSMC differentiation, we hypothesised that Thymosin β4 (Tβ4) may function to maintain healthy vasculature throughout postnatal life. This was supported by the identification of an interaction with Low density lipoprotein receptor related protein 1 (LRP1), an endocytic regulator of PDGF-BB signalling and VSMC proliferation. LRP1 variants have been implicated by genome-wide association studies with risk of AAA and other arterial diseases. Tβ4-null mice displayed aortic VSMC and elastin defects, phenocopying LRP1 mutants, and their compromised vascular integrity predisposed to Angiotensin II-induced aneurysm formation. Aneurysmal vessels were characterised by enhanced VSMC phenotypic modulation and augmented platelet-derived growth factor (PDGF) receptor (PDGFR)β signalling. In vitro, enhanced sensitivity to PDGF-BB, upon loss of Tβ4, associated with dysregulated endocytosis, with increased recycling and reduced lysosomal targeting of LRP1-PDGFRβ. Accordingly, the exacerbated aneurysmal phenotype in Tβ4-null mice was rescued upon treatment with the PDGFRβ antagonist, Imatinib. Our study identifies Tβ4 as a key regulator of LRP1 for maintaining vascular health and provides insights into the mechanisms of growth factor-controlled VSMC phenotypic modulation underlying aortic disease progression.